'Old Mobilities'? Transatlantic Women from the West of Ireland 1880s–1920s. Issue 2 (November 2015) - Walter, Bronwen
The 'new mobilities paradigm' set out by Sheller and Urry (2006) and others urges social scientists to centre many interlocking mobilities in their analyses of contemporary social change, challenging taken-for-granted sedentarism. Drawing on the example of Irish women's chain migration from small farms in the West of Ireland to the East coast of the USA in the late nineteenth and early twentieth centuries, this paper explores a longer history of high levels of mobility. Whilst migration lay at the heart of the movement, it encompassed a much wider range of movements of people, information and material goods. The 'moorings' of women in the their workplace-homes on rural farms and in urban domestic service constituted a gendered immobility, but migration also opened up new opportunities for intra-urban moves, circulatory Transatlantic journeys and upward social mobility. The materiality of such 'old' mobility provides an early baseline against which to assess the huge scale of rapidly-changing hyper-mobility and instantaneous communication in the twenty-first century.